Memahami Tindakan Diskriminasi di Tempat Kerja: Perspektif Hukum dan Etika - Zulia Devi Ananta; Ari Puji Astuti; Putri Ananta Rahayu; Moh Jauhari Ibrahim; M. Isa Anshori (Trending: Jurnal Manajemen dan Ekonomi, 2024)
To properly handle workplace discrimination, it's important to look at it from an ethical and legal standpoint. Discrimination in the workplace is a serious challenge for businesses and organizations. In addition to harming victimized individuals, it can also damage a company's reputation and disrupt productivity and relationships in the workplace. Legal protection, such as ILO Convention No. 111, is essential to safeguard workers' rights and ensure fair labor relations. The ethics of discrimination guides behavior toward others by moral principles such as justice, equality, respect for human dignity, empathy, and social responsibility. This study aims to understand discriminatory actions in the workplace through legal and ethical perspectives using a literature review approach. This literature study approach is carried out by collecting and reviewing theoretical references that are in accordance with the cases obtained. So that the results of the literature review obtained show that law and ethics have an important and necessary role to prevent discrimination in the workplace. The application of ethics and laws is very important in creating a work environment free from discrimination.